Midwifery Education and the Six Pillars of Health Transformation : Challenges, Strategies, and Future Directions - Winerti, Hervina; Susanti, Ari Indra (Jurnal Paedagogy, 2025)
This study aims to analyze the urgency of integrating the six pillars of health transformation—primary care, referral services, health resilience, health financing, human resources for health, and health technology—into midwifery education and to explore the implications and implementation strategies related to policy, curriculum, and institutional governance. The method used is a systematic literature review with data from electronic databases such as Scopus, Google Scholar, PubMed, and ScienceDirect. The instrument employed is a structured literature matrix table, and the data were analyzed using a qualitative descriptive approach to identify thematic patterns and gaps in the existing literature. The findings of this study indicate that integrating the pillars of health transformation into midwifery education is essential for producing graduates who are not only clinically competent but also adaptable to health system dynamics. The results highlight that interprofessional collaboration, digital technologies, experiential learning, and context-based curricula are key components that enhance the quality of midwifery education. The implementation of an Outcome-Based Education (OBE) curriculum is found to be highly relevant for achieving comprehensive graduate competencies, including both clinical and non-clinical skills such as policy literacy and financial literacy. Therefore, reforming midwifery education is a critical strategy to support the sustainable success of health system transformation, particularly in improving maternal and child healthcare services across various settings, including rural and low-resource areas.